NSCA's essentials of tactical strength and conditioning - Alvar, Brent A.; Sell, Katie; Deuster, Patricia A. (Human Kinetics, 2017)
'NSCA's Essentials of Tactical Strength and Conditioning' is the ideal preparatory guide for those seeking TSAC-F certification. The book is also a great reference for fitness trainers who work with tactical populations such as military, law enforcement, and fire and rescue personnel.